Pengaruh Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Pengunjung Eduwisata Lontarsewu Hendrosari - Candra Sugiarto; Woro Utari (Jurnal Ekonomi, Bisnis dan Social, 2024)
Visitor satisfaction is related to visitor perceptions of facilities and service quality. When visitors see that the facilities and service quality do not meet their expectations. The fundamental problem in this research is how the efforts made by tourist object managers to increase visitor satisfaction. The method used in this research design is associative and descriptive method, namely the type of research that seeks the relationship or influence of two or more variables. For the research approach in this thesis using a quantitative research approach. The tool used for data collection in this study was to use a questionnaire as a response from the respondents and the questionnaires will be distributed to the visitors of the Lontarsewu Hendrosari Eduwisata. The data contains the distribution of age, gender, and city origin of the 100 respondents who have been interviewed. First, regarding the age factor, it was found that the majority of respondents were in the age range of 13 to 21 years, as many as 47 people or 47% of the total respondents. Based on the results of research and data analysis, it can be concluded that there is a simultaneous influence of facilities and service quality on visitor satisfaction at the Lontarsewu Hendrosari Educational Tour.